6-5z=26

Simple and best practice solution for 6-5z=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-5z=26 equation:


Simplifying
6 + -5z = 26

Solving
6 + -5z = 26

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -5z = 26 + -6

Combine like terms: 6 + -6 = 0
0 + -5z = 26 + -6
-5z = 26 + -6

Combine like terms: 26 + -6 = 20
-5z = 20

Divide each side by '-5'.
z = -4

Simplifying
z = -4

See similar equations:

| d-258*7=8328 | | (9-3x)=19 | | 5+-3=3t-5 | | 5m^11+3m^8-2m^5=0 | | y-5+y+3y=75 | | 3(x-4)=3(5-5x)+18x | | -5.7x-5.4=-2.3x+4.8 | | -28=2(w+2)-6w | | -.625u+.333=-.125u+1.5 | | 5b^2+4b=0 | | (3x-1)(3x-1)= | | 5v-6=-8v+7 | | (-4x^4y)(x^3y^3)= | | 12(3x+4)-6(2x-2)=4x-80 | | 725.00+10.50x=2.500 | | -6p+6+7p=14 | | 5s^2-6s=0 | | (6x+5)(x^2-4x+1)= | | 3x+2/3=7/2 | | 3x+900=2100 | | 6-(7z-1)=-8(-2z-4)+8 | | x/0.025-2x | | 5x-8(x-4)=23 | | 1950x=72500+1050x | | (3x-2)(3x+8)= | | 4(5y-2)=2y-80 | | 5u-48=8(u-9) | | 1950x=72500+1050 | | -5(-t-2)=5t+1 | | y+1.4y-4.6=2(y-1.7) | | 6x^2-13x-23/2x-7 | | .125(n+6)=-.125(n+2) |

Equations solver categories